A checklist of the Diptera (Insecta) of the Maltese Islands - Ebejer, Martin J.; Gatt, Paul (Zootaxa, 2021)
A checklist is presented of all 986 extant species of Diptera known from the archipelago of the Maltese Islands situated in the central Mediterranean. Species considered to be alien to the Islands are listed with annotations in Appendix 1. The history of dipterology applicable to the islands is outlined and the three important historical published records by Zetterstedt, Rondani and Bezzi & de Stefani-Perez are listed in Appendices 2–4. Species names that are synonyms are indicated where these were used in published records for Malta more or less after the Catalogue of Palaearctic Diptera was published. Species we consider to have been misidentifications are also indicated with an annotation in most cases. Vermileo immaculatus Carles-Tolrá syn. n. & Cuesta-Segura and Vermileo balearicus Wheeler syn. n. are proposed junior synonyms of Vermileo vermileo (Linnaeus).